GAMBARAN PROGRAM PENGENDALIAN MALARIA DI KOTA LUBUK LINGGAU - Purnama, Tri Bayu (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2019)
Indonesia is one of the countries that are endemic to malaria with the prevalence of malaria cases in 2010 at 22.9 per 1000 population. A solution to reduce malaria cases in Indonesia is to develop a malaria elimination program. So based on this issue, the aim of this study was to find out an overview of malaria control programs in LubukLinggau City. The malaria control program in LubukLinggau City had not yet a specific goal in the malaria control program but the program has a technical strategy and activities in the malaria control program. The malaria control program activities carried out are treatment using chloroquine, distribution of insecticide, larvacide bed nets, spraying and laboratory tests. The malaria control program had not yet reached the target that can be seen from AMI and API in 2013 but also had not yet reached the target for LubukLinggau City. Then the problems in the malaria control program are the absence of malaria control programs, no malaria cases treated with ACT, as many as 4.2% of malaria cases were laboratory confirmed and program evaluation only referred to outcome indicators.